Application of The Fuzzy Tsukamoto Method in Determining Household Industry Products - Pasaribu, Nadra Savira; Hardinata, Jata Tata; Qurniawan, Hendry (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2021)
Production system at UD. Mie Akwang is a home industry that provides raw materials for noodle production. Uncertain consumer demand and supplies that are not in accordance with demand make it difficult for this industry to determine the amount of production that will be produced. Previously, this home industry did not have a valid rule to determine the amount of production that must be achieved. Therefore, a decision support system was developed using the Fuzzy Tsukamoto method. This method is the right method in making decisions that use several criteria to produce decisions on the amount of production. In this study, the data used is in the form of data on the amount of production in April 2021. From the calculation process that has been carried out, it can be concluded that if the demand is 28,950 portions and the supply is 30,000 portions, the total production produced is 31,207 portions. The results of these calculations are implemented in the form of a production system and the results obtained are the same, namely 31,207 portions.